Cutaneous nodules in Irrawaddy dolphins: an emerging disease in vulnerable populations - Van Bressem, Marie-Francoise; Minton, Gianna; Sutaria, Dipani; Kelkar, Nachiket; Peter, Cindy; Mohammad, Zulkarnaen; Rubaiyat, M. Mansur; Porter, Lindsay; Rodriguez Vargas, Luz H.; Rajamani, Leela (Inter-Research, 2014)
The presence of cutaneous nodules is reported in vulnerable populations of Irrawaddy dolphins Orcaella brevirostris from Malaysia (Kuching, Bintulu-Similajau, Kinabatangan-Segama and Penang Island), India (Chilika Lagoon) and Bangladesh (Sundarbans). Approximately 5700 images taken for photo-identification studies in 2004 to 2013 were examined for skin disorders. Nodules were detected in 6 populations. They appeared as circumscribed elevations of the skin and varied in size from 2 to >30 mm, were sparse or numerous and occurred on all visible body areas. In 8 photo-identified (PI) dolphins from India and Malaysia, the lesions remained stable (N = 2) or progressed (N = 6) over months but did not regress. The 2 most severely affected individuals were seen in Kuching and the Chilika Lagoon. Their fate is unknown. Cutaneous nodules were sampled in a female that died in a gillnet in Kuching in 2012. Histologically, the lesions consisted of thick collagen bundles covered by a moderately hyperplasic epithelium and were diagnosed as fibropapillomas. Whether the nodules observed in the other O. brevirostris were also fibropapillomas remains to be investigated. Disease prevalence ranged from 2.2% (N = 46; Bintulu-Similajau) to 13.9% (N = 72; Chilika) in 4 populations from Malaysia and India. It was not significantly different in 3 study areas in eastern Malaysia. In Chilika, prevalence was significantly higher (p = 0.00078) in 2009 to 2011 (13.9%) than in 2004 to 2006 (2.8%) in 72 PI dolphins. The emergence of a novel disease in vulnerable O. brevirostris populations is of concern.